Do not worry, be mindful: Effects of induced worry and mindfulness on respiratory variability in a nonanxious population - Vlemincx, Elke (2013)
Generalized Anxiety Disorder (GAD) is characterized by chronic worry. Mindfulness-based stress reduction is thought to remediate excessive worry, because it counteracts a permanent defense state of enhanced vigilance to potential threats. The present study aimed to compare respiratory variability (RV) during worry and mindfulness. Following an 8-minute baseline, 37 healthy participants underwent 11-min worry and mindfulness inductions, in randomized order, using auditory scripts. Respiration was measured by chest and abdominal inductance belts. RV was quantified by (1) autocorrelation to assess linear breathing variability, (2) sample entropy to assess nonlinear breathing variability. Compared to baseline and mindfulness, worry showed decreased autocorrelation in all respiratory parameters and compared to mindfulness, worry showed decreased entropy in respiratory rate. These results suggest that, in contrast to mindfulness, worry is characterized by decreased respiratory stability and flexibility, and therefore worry and mindfulness seem to have countering effects on RV and respiratory regulation.